Generalized Estimator of Finite population Variance - A.K.P.C. Swain (Journal of Statistical Theory and Applications (JSTA), 2015)
In this paper a generalized class of finite population variance is suggested and its large sample bias and mean square error are derived. Further some special cases of this class are considered along with a numerical example to compute and compare their biases and mean square errors.